2019
DOI: 10.3201/eid2511.181844
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influenza and Avian Influenza A(H5N1) Virus Surveillance among Inpatients and Outpatients, East Jakarta, Indonesia, 2011–2014

Abstract: During October 2011–September 2014, we screened respiratory specimens for seasonal and avian influenza A(H5N1) virus infections among outpatients with influenza-like illness and inpatients with severe acute respiratory infection (SARI) in East Jakarta, an Indonesia district with high incidence of H5N1 virus infection among poultry. In total, 31% (1,875/6,008) of influenza-like illness case-patients and 15% (571/3,811) of SARI case-patients tested positive for influenza virus. Influenza A(H1N1)pdm09, influenza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
4
1
2
Order By: Relevance
“…In these studies, the average reported prevalence of AIV in humans was 16.3%. The reported prevalence ranged in these studies 1-44% (35)(36)(37). A prior study among poultry workers in Iran found a 17% prevalence of avian influenza in exposed individuals and a 3% prevalence in nonexposed individuals, which differed from our findings (54).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In these studies, the average reported prevalence of AIV in humans was 16.3%. The reported prevalence ranged in these studies 1-44% (35)(36)(37). A prior study among poultry workers in Iran found a 17% prevalence of avian influenza in exposed individuals and a 3% prevalence in nonexposed individuals, which differed from our findings (54).…”
Section: Discussioncontrasting
confidence: 93%
“…The avian influenza subtype H5N1 was reported only in one patient. According to the findings of this study, seasonal influenza was found to be more prevalent than avian influenza (37).…”
Section: Avian Influenza In Humanmentioning
confidence: 53%
“…The highly pathogenic avian influenza virus (HPAI) A(H5N1) has been circulating since 2003 in Indonesia, with significant impacts on poultry health, severe economic losses, and 168 fatal laboratory-confirmed human cases (Karo-Karo et al, 2019). It was emphasized again with an October 2011-September 2014 study, which screened respiratory specimens for seasonal influenza A (H5N1) virus infection and poultry among outpatients with influenza-like illness and hospitalized patients with severe acute respiratory infections (SARI) in East Jakarta, a district in Indonesia with a high incidence of H5N1 virus infection among poultry (Lafond et al, 2019). The film Aruna dan Lidahnya is a spectacle not only limited to functioning as entertainment but also raises important issues related to culture, cuisine, and health.…”
Section: Resultsmentioning
confidence: 99%
“…Dalam studi tahun 2019 terkait kejadian In uenza Like Illness (ILI) & Severe Acute Respiratory Infection (SARI) di Jakarta Timur, jumlah persentase kontribusi influenza signifikan (31% pada ILI, 15% pada SARI). 3 Total insiden kasus flu di Indonesia diperkirakan mencapai 4 juta kasus setiap tahun dan mengakibatkan hampir 200.000 rawat inap terkait dengan flu. 4 Influenza dianggap identik dengan infeksi saluran pernapasan.…”
Section: Pendahuluanunclassified